PENGARUH SAFETY MANAGEMENT PRACTICES TERHADAP SAFETY PERFORMANCE DENGAN VARIABEL MEDIASI SAFETY KNOWLEDGE DAN SAFETY MOTIVATION (Studi pada Pelaksana Produksi Pabrik III PT Petrokimia Gresik) - Rosalita, Novi Aditya; Ratmawati, Dwi; Agustina, Tri Siwi (IQTISHODUNA, 2015)
Safety management practices not only improve working conditions but also positively influenceemployees, attitudes and behaviors with regard to safety, thereby reducing accidents in workplace. Thisstudy measured employees’ perceptions on six safety management practices and self-reported safety knowledge,safety motivation, safety compliance and safety participation. The study conducts a survey by usingquestionnaire among 69 Pelaksana Produksi Pabrik III (Executive Production Factory) PT. Petrokimia Gresik.The reliability and validity of all the indicators were found acceptable. The data are analyzed using PartialLeast Square (PLS) with SmartPLS version 2.0.The result is safety management practices have direct andsignificant influence to safety performance, safety management practices have indirect and significant influenceto safety performance through safety knowledge, and safety management practices have indirect influence tosafety performance through safety motivation.